A multi-stage coated lithium iron manganese phosphate positive electrode material and a preparation method and application thereof

CN120809773BActive Publication Date: 2026-10-23FUAN QINGMEI ENERGY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510869809.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2026-10-23
Estimated Expiration
2045-06-26

AI Technical Summary

Technical Problem

[0004]本发明的目的在于,提供一种多级包覆的磷酸锰铁锂正极材料及其制备方法和应用,用于解决现有技术的磷酸锰铁锂正极材料存在制造成本高、导电性差和高温循环稳定性差等技术问题

Benefits of technology

[0015]本发明的有益效果是:区别于现有技术的情况,本发明提供了一种多级包覆的磷酸锰铁锂正极材料及其制备方法和应用,上述磷酸锰铁锂正极材料为核壳结构,核壳结构包括核芯、包裹于核芯表面的内包覆层、包裹于内包覆层表面的中间包覆层以及包裹于中间包覆层表面的外包覆层,其中,核芯包括LiMn1-xFexPO4层,内包覆层包括氮掺杂碳层,中间包覆层包括三维碳纳米管/石墨烯导电网络,外包覆层包括Al2O3层。本发明提供的核壳结构的磷酸锰铁锂正极材料中:核芯采用LiMn1-xFexPO4层,内包覆层的氮掺杂碳层可提升材料整体导电性;中间包覆层的三维碳纳米管/石墨烯导电网络可进一步构建高效电子传输通道,增强导电性;外包覆层的Al2O3层则针对性抑制锰溶出,解决高温循环稳定性差的问题。同时,上述制备方法突破了传统包覆技术在精度和效果上的限制,既改善了材料的电子/离子电导率、抑制锰溶出,提升高温循环稳定性,又通过创新工艺为产业化生产提供了更优的技术路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120809773B_ABST
    Figure CN120809773B_ABST
Patent Text Reader

Abstract

The application provides a multi-stage coated lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. 1‑x Fe x PO4 layer, a nitrogen-doped carbon layer wrapped on the surface of the LiMn 1‑ x Fe x PO4 layer, a three-dimensional carbon nanotube / graphene conductive network wrapped on the surface of the nitrogen-doped carbon layer and an Al2O3 layer wrapped on the surface of the three-dimensional carbon nanotube / graphene conductive network. In the lithium manganese iron phosphate positive electrode material provided by the application, the nitrogen-doped carbon layer can improve the overall conductivity of the material; the three-dimensional carbon nanotube / graphene conductive network of the intermediate coating layer can further construct an efficient electron transmission channel and enhance the conductivity; and the Al2O3 layer of the outer coating layer can specifically inhibit manganese dissolution and solve the problem of poor high-temperature cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a multi-level coated lithium manganese iron phosphate cathode material, its preparation method, and its application. Background Technology

[0002] Lithium manganese iron phosphate (LMFP) combines the advantages of a high voltage platform (4.1V) and low cost, but its application is limited by problems such as manganese leaching, low electronic / ionic conductivity, and poor high-temperature cycling stability. Existing technologies mainly improve performance through doping, carbon coating, or structural optimization. For example, Defang Nano uses polymer nanospheres to control material morphology, improving compaction density and conductivity; Hunan Yuneng uses a composite film of phenolic nanocellulose and SiO2 nanotubes to suppress manganese leaching; and Xinyangfeng optimizes electrical performance by achieving particle classification through batch sand milling of slurry. However, existing methods still have the following problems: high raw material costs, insufficient utilization of industrial by-products; a single coating layer cannot simultaneously solve manganese leaching and conductivity defects; and high-temperature sintering processes require sophisticated equipment and consume a lot of energy.

[0003] Therefore, there is an urgent need for a multi-stage coated lithium manganese iron phosphate cathode material, its preparation method, and its application to solve the above-mentioned technical problems. Summary of the Invention

[0004] The purpose of this invention is to provide a multi-stage coated lithium manganese iron phosphate cathode material, its preparation method, and its application, in order to solve the technical problems of existing lithium manganese iron phosphate cathode materials, such as high manufacturing cost, poor conductivity, and poor high-temperature cycling stability.

[0005] To solve the above technical problems, the present invention provides a multi-level coated lithium manganese iron phosphate cathode material. The lithium manganese iron phosphate cathode material has a core-shell structure, which includes a core, an inner coating layer wrapped around the surface of the core, an intermediate coating layer wrapped around the surface of the inner coating layer, and an outer coating layer wrapped around the surface of the intermediate coating layer. The core includes LiMn 1-x Fe x The PO4 layer consists of an inner cladding layer comprising a nitrogen-doped carbon layer, an intermediate cladding layer comprising a three-dimensional carbon nanotube / graphene conductive network, and an outer cladding layer comprising an Al2O3 layer; 0 < x < 1.

[0006] Accordingly, the present invention also provides a method for preparing the above-mentioned multi-stage coated lithium manganese iron phosphate cathode material, the method comprising the following steps: S10, after mixing iron source, manganese source and phosphorus source, a precipitant is added to carry out a co-precipitation reaction to obtain iron-manganese-phosphorus precursor; S20, the iron-manganese-phosphorus precursor is mixed with polydopamine solution and then subjected to self-polymerization reaction to obtain polydopamine-coated iron-manganese-phosphorus precursor. S30 involves ball milling a polydopamine-coated iron-manganese-phosphorus precursor, carbon nanotubes, and graphene dispersion to form a first conductive composite structure with a double-layer coating of the iron-manganese-phosphorus precursor. S40, the first conductive composite structure is mixed with a lithium source and then subjected to gradient sintering to obtain a second conductive composite structure with double-layer coating of lithium manganese iron phosphate. S50, after pulverizing the second conductive composite structure, an Al2O3 layer is deposited on the second conductive composite structure to obtain lithium manganese iron phosphate cathode material.

[0007] Preferably, in step S10: the iron source and manganese source are selected from the iron-manganese solution obtained from the titanium dioxide production process, and the iron-manganese solution includes ferrous sulfate and manganese sulfate.

[0008] Preferably, in step S10: the phosphorus source includes phosphoric acid or phosphate, the precipitant includes ammonia, and the reaction pH during the co-precipitation reaction is 2.5~3.5.

[0009] Preferably, in step S20: the temperature for the self-polymerization reaction is 40~80℃, and the time is 4~8h; the thickness of the polydopamine layer in the polydopamine-coated iron-manganese-phosphorus precursor is 10~30nm.

[0010] Preferably, in step S30: the first conductive composite structure includes an iron-manganese-phosphorus precursor, a polydopamine layer coated on the surface of the iron-manganese-phosphorus precursor, and a three-dimensional carbon nanotube / graphene conductive network wrapped on the surface of the polydopamine layer.

[0011] Preferably, step S40 specifically includes: S401, the first conductive composite structure is mixed with a lithium source and heated to 350~450℃ in an inert atmosphere and held for 1~3h to obtain a conductive network intermediate with a nitrogen-doped carbon layer. S402, the conductive network intermediate is heated to 600~800℃ in an inert atmosphere and held for 7~10h to obtain the second conductive composite structure.

[0012] Preferably, in step S40: the second conductive composite structure includes LiMn 1-x Fe x PO4 layer, coated with LiMn 1-x Fe x Nitrogen-doped carbon layer on the surface of PO4 layer and three-dimensional carbon nanotube / graphene conductive network wrapped around the surface of nitrogen-doped carbon layer.

[0013] Preferably, in step S50: the D50 particle size of the second conductive composite structure after pulverization is 1~2μm; the thickness of the Al2O3 layer in the lithium manganese iron phosphate cathode material is 1~5nm.

[0014] Accordingly, the present invention also provides the application of lithium manganese iron phosphate cathode material prepared by the above-mentioned method or the multi-level coated lithium manganese iron phosphate cathode material as described above in the preparation of lithium batteries.

[0015] The beneficial effects of this invention are as follows: Unlike existing technologies, this invention provides a multi-stage coated lithium manganese iron phosphate cathode material, its preparation method, and its application. The aforementioned lithium manganese iron phosphate cathode material has a core-shell structure, comprising a core, an inner coating layer surrounding the surface of the core, an intermediate coating layer surrounding the surface of the inner coating layer, and an outer coating layer surrounding the surface of the intermediate coating layer. The core comprises LiMn... 1-x Fe x The core-shell structure of the lithium manganese iron phosphate cathode material provided by this invention comprises a PO4 layer, an inner coating layer including a nitrogen-doped carbon layer, a middle coating layer including a three-dimensional carbon nanotube / graphene conductive network, and an outer coating layer including an Al2O3 layer. 1-x Fe x The PO4 layer and the nitrogen-doped carbon layer of the inner coating enhance the overall conductivity of the material; the three-dimensional carbon nanotube / graphene conductive network of the middle coating further constructs efficient electron transport channels, enhancing conductivity; and the Al2O3 layer of the outer coating specifically inhibits manganese dissolution, solving the problem of poor high-temperature cycling stability. Simultaneously, the above preparation method overcomes the limitations of traditional coating techniques in terms of precision and effectiveness, improving the material's electronic / ionic conductivity, inhibiting manganese dissolution, and enhancing high-temperature cycling stability, while also providing a superior technical path for industrial production through innovative processes. Attached Figure Description

[0016] Figure 1 A flowchart illustrating the preparation method of the multi-stage coated lithium manganese iron phosphate cathode material provided in this embodiment of the invention; Figure 2 The XRD pattern of the multi-stage coated lithium manganese iron phosphate cathode material provided in Example 1; Figure 3 This is a SEM image of the lithium manganese iron phosphate material obtained in Example 1 of the present invention. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a multi-stage coated lithium manganese iron phosphate cathode material, its preparation method, and its application. Specifically, it relates to a high-performance lithium manganese iron phosphate (LiMn) cathode material using titanium dioxide industrial by-products as raw materials and incorporating multi-stage coating technology. 1-x Fe x Preparation methods and applications of PO4 (LMFP) cathode materials.

[0019] The present invention first provides a multi-level coated lithium manganese iron phosphate cathode material. The lithium manganese iron phosphate cathode material has a core-shell structure, which includes a core, an inner coating layer wrapped around the surface of the core, an intermediate coating layer wrapped around the surface of the inner coating layer, and an outer coating layer wrapped around the surface of the intermediate coating layer. The core includes LiMn 1-x Fe x The PO4 layer consists of an inner cladding layer comprising a nitrogen-doped carbon layer, an intermediate cladding layer comprising a three-dimensional carbon nanotube / graphene conductive network, and an outer cladding layer comprising an Al2O3 layer; 0 < x < 1.

[0020] This invention addresses the challenges of conductivity, manganese leaching, and process cost in lithium manganese iron phosphate (LiFePO4) through a multi-level core-shell coating structure and nanoscale modification technology. Specifically, the core uses LiMn... 1-x Fe x The PO4 layer lays the foundation for the high-voltage platform; the inner nitrogen-doped carbon layer optimizes the electron transport path through nitrogen atom doping, thereby improving intrinsic conductivity; the three-dimensional carbon nanotube / graphene conductive network in the middle layer constructs a continuous conductive channel, further reducing the interface resistance; the outer Al2O3 layer inhibits manganese ion dissolution through physical barrier and chemical stabilization, thereby enhancing high-temperature cycling stability.

[0021] Please see Figure 1 The present invention also provides a method for preparing the above-mentioned multi-stage coated lithium manganese iron phosphate cathode material, the method comprising the following steps: S10 involves mixing iron, manganese, and phosphorus sources, then adding a precipitant to induce a co-precipitation reaction, yielding an iron-manganese-phosphorus precursor.

[0022] Specifically, step S10 also includes: Using byproducts from titanium dioxide production as iron and manganese sources, an iron-manganese-phosphorus precursor (Fe) was generated via ammonia co-precipitation. x Mn 1-x PO4·2H2O, 0 < x < 1, the reaction pH is controlled at 2.5~3.5 to avoid the introduction of impurities.

[0023] Specifically, the iron and manganese sources are selected from the iron-manganese solution obtained from the titanium dioxide production process, which includes ferrous sulfate and manganese sulfate; the phosphorus source includes phosphoric acid or phosphate, and the precipitant includes ammonia.

[0024] Specifically, this invention uses a mixed solution of ferrous sulfate and manganese sulfate, byproducts of titanium dioxide production, as the iron and manganese sources. Through ammonia co-precipitation, an iron-manganese-phosphorus precursor is prepared under conditions of pH 2.5-3.5. This not only achieves high-value utilization of industrial waste and significantly reduces raw material costs, but also precisely controls reaction conditions to avoid the introduction of impurities and ensures the purity of the precursor, providing a high-quality foundation for the subsequent synthesis of high-performance multi-stage coated lithium iron phosphate cathode materials.

[0025] In one embodiment, the chemical formula of the iron-manganese-phosphorus precursor is Fe. 0.5 Mn 0.5 PO4·2H2O.

[0026] S20, the iron-manganese-phosphorus precursor is mixed with a polydopamine solution and subjected to a self-polymerization reaction to obtain a polydopamine-coated iron-manganese-phosphorus precursor.

[0027] Specifically, step S20 also includes: Iron-manganese-phosphorus precursors were mixed with polydopamine (PDA) solution, and a 10-30 nm PDA layer was formed on the particle surface through a self-polymerization reaction to obtain polydopamine-coated iron-manganese-phosphorus precursors (PDA@Fe). x Mn 1-x PO4·2H2O) to enhance the ion diffusion rate; wherein, the temperature for the self-polymerization reaction is 40~80℃ and the time is 4~8h.

[0028] Specifically, this process utilizes a controlled self-polymerization reaction under mild conditions to significantly enhance the ion diffusion rate without damaging the precursor structure, taking advantage of the high ion affinity and nanoscale thickness of the PDA layer. This lays the foundation for improving the overall ionic conductivity of the material in subsequent multi-level coating structures. At the same time, this method is simple to operate, operates under mild conditions, requires no complex equipment, and is suitable for industrial production processes, effectively solving the problem of balancing performance improvement and process feasibility in traditional methods.

[0029] S30 involves ball milling a polydopamine-coated iron-manganese-phosphorus precursor, carbon nanotubes, and graphene dispersion to form a first conductive composite structure with a double-layer coating of the iron-manganese-phosphorus precursor.

[0030] Specifically, step S30 also includes: The PDA-coated precursor was ball-milled with carbon nanotubes (CNTs) and graphene dispersion to form a three-dimensional conductive network. The ball milling speed was 600~1000 r / min (preferably 800 r / min) for 3~5 h (preferably 4 h). The first conductive composite structure (three-dimensional carbon nanotube / graphene conductive network@PDA@Fe) was formed. x Mn 1-xPO4·2H2O) includes an iron-manganese-phosphorus precursor, a polydopamine layer coated on the surface of the iron-manganese-phosphorus precursor, and a three-dimensional carbon nanotube / graphene conductive network wrapped on the surface of the polydopamine layer.

[0031] Specifically, this process achieves efficient composite formation of carbon nanotubes and graphene outside the polydopamine layer by optimizing ball milling parameters, constructing a continuous and dense electron transport channel and significantly improving the electronic conductivity of the material. The polydopamine layer, as an intermediate transition layer, enhances the interfacial bonding force between the carbon material and the precursor, further reducing the interfacial resistance. At the same time, this ball milling composite process is controllable and low-cost, providing a feasible solution for the large-scale preparation of highly conductive lithium manganese iron phosphate cathode materials, effectively solving the problems of insufficient conductivity improvement and poor interfacial compatibility in traditional methods.

[0032] S40, the first conductive composite structure is mixed with a lithium source and then subjected to gradient sintering to obtain a second conductive composite structure with double-layer coating of lithium manganese iron phosphate.

[0033] Specifically, step S40 also includes: S401, the first conductive composite structure is mixed with a lithium source at a molar ratio of 1:(1.01~1.1, preferably 1.05), and then heated to 350~450℃ (e.g. 400℃) at 2℃ / min under an inert atmosphere (e.g., nitrogen atmosphere) and held for 1~3h (e.g. 2h) to obtain a conductive network intermediate with a nitrogen-doped carbon layer (three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon layer@Fe). x Mn 1-x PO4·2H2O); S402, the conductive network intermediate is heated to 600~800℃ (e.g. 750℃) in an inert atmosphere (e.g., argon atmosphere) and held at that temperature for 7~10h (e.g., 8h) to promote LiMn x Fe 1-x After the formation of the PO4 (0 < x < 1) lattice and the stabilization of the three-dimensional carbon nanotube / graphene conductive network, a second conductive composite structure (three-dimensional carbon nanotube / graphene conductive network @ nitrogen-doped carbon layer @ LiMn) is obtained. 1-x Fe x PO4).

[0034] Specifically, the second conductive composite structure includes LiMn 1-x Fe x PO4 layer, coated with LiMn 1-x Fe x Nitrogen-doped carbon layer on the surface of PO4 layer and three-dimensional carbon nanotube / graphene conductive network wrapped around the surface of nitrogen-doped carbon layer.

[0035] Specifically, this step achieves synergistic control of nitrogen-doped carbon layer construction and lattice optimization through a two-stage temperature-controlled sintering process under an inert atmosphere: In the low-temperature range (350~450℃): after the lithium source is mixed with the first conductive composite structure, the polydopamine (PDA) layer is pyrolyzed into a nitrogen-doped carbon layer through slow heating (2℃ / min) and heat preservation treatment. Nitrogen atom doping significantly improves the intrinsic conductivity of the carbon layer, while excess lithium source compensates for lithium volatilization during sintering, ensuring the core LiMn 1-x Fe x The accuracy of the stoichiometry of PO4; At high temperatures (600~800℃): An argon atmosphere promotes the full development of the olivine lattice and simultaneously stabilizes the three-dimensional carbon nanotube / graphene conductive network, preventing carbon structure collapse or aggregation at high temperatures. This forms a dual conductive channel of "nitrogen-doped carbon layer - three-dimensional carbon network," significantly reducing interfacial resistance. This process overcomes the energy consumption bottleneck of traditional single high-temperature sintering through segmented temperature control. Lattice integrity and conductive network stabilization can be achieved at 750℃, reducing the sintering temperature by 50~100℃ compared to traditional processes. Simultaneously, the synergistic effect of nitrogen-doped carbon and the three-dimensional carbon network increases the material's electronic conductivity by 2~3 orders of magnitude, effectively solving the problems of high energy consumption and poor conductive network stability in existing technologies.

[0036] S50, after pulverizing the second conductive composite structure, an Al2O3 layer is deposited on the second conductive composite structure to obtain lithium manganese iron phosphate cathode material.

[0037] Specifically, step S50 also includes: The second conductive composite structure (sintered product) is pulverized by airflow to D50=1~2μm, and an Al2O3 layer of 1~5nm (preferably 2nm) is deposited on the surface by atomic layer deposition (ALD) to further suppress manganese leaching.

[0038] Specifically, this invention precisely controls the particle size of the sintered product to D50 = 1~2μm through airflow pulverization, and then uses atomic layer deposition (ALD) technology to uniformly coat the surface with an Al2O3 layer of 1~5nm. This not only increases the specific surface area and optimizes the interfacial contact by refining the particle size, but also forms a dense Al2O3 physical barrier with the atomic-level deposition precision of ALD technology. This effectively blocks the electrolyte from corroding the active material and inhibits the dissolution of manganese ions. At the same time, the low-temperature process avoids damage to the internal three-dimensional conductive network, thus balancing the high-temperature cycling stability of the material with the improvement of conductivity. This solves the contradiction between inhibiting manganese dissolution and maintaining conductivity in the prior art.

[0039] Accordingly, the present invention also provides the application of lithium manganese iron phosphate cathode material prepared by the above-mentioned method or the multi-level coated lithium manganese iron phosphate cathode material as described above in the preparation of lithium batteries.

[0040] The technical solution of this application will now be described in further detail with reference to specific embodiments.

[0041] Example 1: Embodiment 1 of this invention first provides a multi-level coated lithium manganese iron phosphate cathode material, which has a core-shell structure (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 PO4), the core-shell structure includes a core, an inner cladding layer covering the surface of the core, an intermediate cladding layer covering the surface of the inner cladding layer, and an outer cladding layer covering the surface of the intermediate cladding layer; The core includes LiMn 0.5 Fe 0.5 The PO4 layer consists of an inner cladding layer comprising a nitrogen-doped carbon layer, an intermediate cladding layer comprising a three-dimensional carbon nanotube / graphene conductive network, and an outer cladding layer comprising an Al2O3 layer.

[0042] Embodiment 1 of the present invention also provides a method for preparing a multi-stage coated lithium manganese iron phosphate cathode material, the specific steps of which include the following: Step 1, Raw material pretreatment: Take 1000g of titanium dioxide byproduct (a mixed solution of ferrous sulfate and manganese sulfate, Fe:Mn molar ratio 1:1), add ammonia water to adjust the pH to 3.0, stir and react for 4 hours, and after centrifugation, washing and drying, obtain the iron-manganese-phosphorus precursor Fe. 0.5 Mn 0.5 PO4·2H2O.

[0043] Step 2, Inner Coating: The iron-manganese-phosphorus precursor Fe... 0.5 Mn 0.5 PO4·2H2O was mixed with a 0.5wt% polydopamine (PDA) solution and subjected to self-polymerization at 60°C for 6 hours to form a polydopamine-coated iron-manganese-phosphorus precursor (PDA@Fe). 0.5 Mn 0.5 PO4·2H2O) In this process, the PDA layer is approximately 15 nm thick.

[0044] Step 3, Outer Coating: The polydopamine-coated iron-manganese-phosphorus precursor was ball-milled with a dispersion of 1 wt% carbon nanotubes (CNTs) and 0.5 wt% graphene at 800 r / min for 4 h to form a first conductive composite structure with a double-layer coating of the iron-manganese-phosphorus precursor (three-dimensional carbon nanotube / graphene conductive network @PDA @Fe). 0.5 Mn 0.5PO4·2H2O).

[0045] Step 4, Low-temperature sintering: The first conductive composite structure is mixed with Li2CO3 at a molar ratio of 1:1.05, and heated to 400℃ at a rate of 2℃ / min under a nitrogen atmosphere, and held for 2 hours to obtain a conductive network intermediate with a nitrogen-doped carbon layer (three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon layer@Fe). 0.5 Mn 0.5 PO4·2H2O).

[0046] Step 5, High-temperature sintering: The conductive network intermediate is heated to 750℃ and held at that temperature for 8 hours under an argon atmosphere to promote the LiMn... 0.5 Fe 0.5 After the formation of the PO4 lattice and stabilization of the three-dimensional carbon nanotube / graphene conductive network, a second conductive composite structure (three-dimensional carbon nanotube / graphene conductive network @ nitrogen-doped carbon layer @ LiMn) is obtained. 0.5 Fe 0.5 PO4).

[0047] Step Six, Post-processing: The second conductive composite structure is pulverized by airflow to D 50 =1.1μm, an Al2O3 layer of 2nm was deposited on the surface using atomic layer deposition (ALD) to obtain a lithium manganese iron phosphate cathode material with multi-level coating (Al2O3@3D carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 PO4).

[0048] Please see Figure 2 , Figure 2 The XRD (X-ray diffraction) pattern of the multi-stage coated lithium manganese iron phosphate cathode material provided in Example 1; Figure 2 The XRD pattern shows typical olivine-type LiMn 1-x Fe x The characteristic diffraction peaks of PO4, with sharp main peaks and no impurity peaks, indicate that the core material has high crystallinity and that Fe / Mn elements are uniformly dissolved to form a single solid solution phase. The nitrogen-doped carbon layer and Al2O3 coating layer are amorphous structures, with no obvious characteristic peaks in the XRD pattern, but a slight broadening of the base peak may be observed, indicating the uniform presence of the amorphous coating layer.

[0049] Please see Figure 3 , Figure 3 This is a SEM image of the lithium manganese iron phosphate material obtained in Example 1 of the present invention; Figure 3SEM images confirmed that the lithium manganese iron phosphate cathode material has a uniform, near-spherical particle morphology (D50 = 1~2 μm). A continuous three-dimensional carbon nanotube / graphene conductive network was successfully constructed on its surface, and a 1~5 nm Al2O3 layer was uniformly coated using ALD technology. Each coating layer and the core LiMn... 0.5 Fe 0.5 The PO4 interface is tightly bonded without delamination, which directly verifies the controllability and integrity of the multi-level coating structure, and provides microstructural basis for the material's high conductivity, manganese leaching inhibition and high-temperature cycling stability.

[0050] Example 2: Example 2 of this invention provides a multi-level coated lithium manganese iron phosphate cathode material (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 The preparation method of lithium manganese iron phosphate cathode material (PO4) is largely the same as that in Example 1 of this invention, except that: Step 2, Inner Coating: The iron-manganese-phosphorus precursor Fe... 0.5 Mn 0.5 PO4·2H2O was mixed with 0.5wt% polydopamine (PDA) solution and subjected to self-polymerization at 60℃ for 8 hours to form a polydopamine-coated iron-manganese-phosphorus precursor (PDA@Fe). 0.5 Mn 0.5 (PO4·2H2O) In this process, the PDA layer is approximately 20 nm thick.

[0051] Example 3: Example 3 of this invention provides a multi-level coated lithium manganese iron phosphate cathode material (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 The preparation method of lithium manganese iron phosphate cathode material (PO4) is largely the same as that in Example 1 of this invention, except that: Step 3, Outer Coating: The polydopamine-coated iron-manganese-phosphorus precursor was ball-milled with a dispersion of 1.5 wt% carbon nanotubes (CNTs) and 0.5 wt% graphene (i.e., the mass ratio of CNTs to graphene was 3:1) at a ball milling speed of 800 r / min for 4 h, forming a first conductive composite structure with a double-layer coating of the iron-manganese-phosphorus precursor (three-dimensional carbon nanotube / graphene conductive network @PDA @Fe). 0.5 Mn 0.5 PO4·2H2O).

[0052] Example 4: Example 4 of this invention provides a multi-level coated lithium manganese iron phosphate cathode material (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 The preparation method of lithium manganese iron phosphate cathode material (PO4) is largely the same as that in Example 1 of this invention, except that: Step 5, High-temperature sintering: The conductive network intermediate is heated to 700℃ and held at that temperature for 8 hours under an argon atmosphere to promote the LiMn... 0.5 Fe 0.5 After the formation of the PO4 lattice and stabilization of the three-dimensional carbon nanotube / graphene conductive network, a second conductive composite structure (three-dimensional carbon nanotube / graphene conductive network @ nitrogen-doped carbon layer @ LiMn) is obtained. 0.5 Fe 0.5 PO4).

[0053] Example 5: Example 5 of this invention provides a multi-level coated lithium manganese iron phosphate cathode material (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 The preparation method of lithium manganese iron phosphate cathode material (PO4) is largely the same as that in Example 1 of this invention, except that: Step Six, Post-processing: The second conductive composite structure is pulverized by airflow to D 50 =1.1μm, an Al2O3 layer of 3nm was deposited on the surface using atomic layer deposition (ALD) to obtain a lithium manganese iron phosphate cathode material with multi-level coating (Al2O3@3D carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 PO4).

[0054] Comparative Example 1: Comparative Example 1 provides a single carbon-coated lithium manganese iron phosphate cathode material and its preparation method. The specific steps of the preparation method are as follows: Step 1, Raw material pretreatment: Take 1000g of titanium dioxide byproduct (a mixed solution of ferrous sulfate and manganese sulfate, Fe:Mn molar ratio 1:1), add ammonia water to adjust the pH to 3.0, stir and react for 4 hours, and after centrifugation, washing and drying, obtain the iron-manganese-phosphorus precursor Fe. 0.5 Mn 0.5 PO4·2H2O.

[0055] Step 2, Coating: Coating the Fe, manganese, and phosphorus precursor with Fe 0.5 Mn 0.5PO4·2H2O was mixed with glucose as a carbon source and carbonized at 800℃ for 4 hours to form a single carbon-coated iron-manganese-phosphorus precursor (single C source @ Fe). 0.5 Mn 0.5 PO4·2H2O).

[0056] Step 3, High-temperature sintering: The single carbon-coated iron-manganese-phosphorus precursor is heated to 750℃ and held for 8 hours in an argon atmosphere to promote the LiMn... 0.5 Fe 0.5 PO4 lattice formation yields a single carbon-coated lithium manganese iron phosphate cathode material (single C source @ LiMn). 0.5 Fe 0.5 PO4).

[0057] Comparative Example 2: Comparative Example 2 provides a multi-level coated lithium manganese iron phosphate cathode material (Al2O3@three-dimensional carbon nanotube / graphene conductive network@nitrogen-doped carbon@LiMn). 0.5 Fe 0.5 The preparation method of lithium manganese iron phosphate cathode material (PO4) is largely the same as that in Example 1 of this invention, except that: Step 1, Raw material pretreatment: 1000g of a mixed solution of pure ferrous sulfate and manganese sulfate (without using titanium dioxide byproducts, Fe:Mn molar ratio 1:1) was used. Ammonia was added to adjust the pH to 3.0, and the mixture was stirred for 4 hours. After centrifugation, washing, and drying, the iron-manganese-phosphorus precursor Fe was obtained. 0.5 Mn 0.5 PO4·2H2O.

[0058] Specifically, the lithium manganese iron phosphate cathode materials prepared in Examples 1-5 and Comparative Examples 1-2 were used to prepare cathode sheets, which were then combined with lithium metal sheets, polypropylene separators, and lithium hexafluorophosphate electrolyte to form lithium-ion batteries. The electrochemical performance of the lithium-ion batteries was then tested. The charge-discharge conditions were as follows: at a temperature of 25°C, the battery was first charged at a constant current of 0.1C to a voltage of 4.5V, then charged at a constant voltage of 4.5V to a current of 0.05C, and then discharged at a constant current of 0.1C to a voltage of 2.5V. This constituted one charge-discharge cycle at a rate of 0.1C. Then, a second and third charge-discharge cycle were performed at rates of 0.2C and 0.5C, respectively, to fully activate the battery. After this, the battery was charged and discharged 200 times at a rate of 1C, and the discharge capacity after 200 cycles was measured to obtain the capacity retention rate.

[0059] Furthermore, the electrochemical performance test results of the lithium-ion batteries prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention are shown in Table 1 below: Table 1. Electrochemical performance test results of lithium-ion batteries prepared in each group.

[0060] Specifically, as shown in Table 1, the lithium-ion batteries prepared in Examples 1 to 5 have better 1C discharge capacity and better capacity retention after 200 cycles compared to the lithium-ion battery prepared in Comparative Example 1. This indicates that the lithium-ion battery prepared with the multi-stage coated lithium manganese iron phosphate cathode material provided by the present invention has superior electrochemical performance compared to the lithium-ion battery prepared with the single carbon coated lithium manganese iron phosphate cathode material.

[0061] Specifically, comparing Example 2 with Example 1 shows that a thicker PDA layer enhances ion diffusion in the lithium iron phosphate cathode material, leading to improved cycle stability of the prepared lithium-ion battery. Comparing Example 3 with Example 1 shows that the lithium iron phosphate cathode material prepared with high CNT content can improve conductivity, further optimizing the compaction density of the prepared lithium-ion battery. Comparing Example 4 with Example 1 shows that using a lower temperature in the high-temperature sintering step can slightly reduce the 1C discharge capacity, but reduces energy consumption by 10%. Comparing Example 5 with Example 1 shows that the lithium iron phosphate cathode material prepared with a thicker Al2O3 layer significantly inhibits manganese dissolution, resulting in the best capacity retention rate of the prepared lithium-ion battery after 200 cycles. Comparing Comparative Example 2 with Example 1 shows that the electrochemical performance of lithium-ion batteries prepared with traditional iron-nickel raw materials is close to that of lithium-ion batteries prepared using titanium dioxide byproducts, but the cost is significantly higher and the environmental friendliness is insufficient.

[0062] This technical solution systematically verifies the synergistic effect of multi-level coating technology, gradient sintering process, and atomic layer deposition (ALD) surface modification in the preparation of lithium manganese iron phosphate (LMFP) cathode materials through experiments, and reveals the influence mechanism of key parameters on material performance: the synergistic optimization of multi-level coating and gradient sintering (Example 1) adopts a 15nm polydopamine (PDA) inner layer coating combined with a CNT / graphene three-dimensional conductive network, which significantly improves ion / electron transport efficiency; the gradient sintering process (400℃ nitrogen pre-carbonization → 750℃ argon lattice reconstruction) simultaneously optimizes the crystallinity and lattice stability of the carbon layer; the ALD deposition of a 2nm Al2O3 layer suppresses manganese dissolution, achieving a 1C discharge capacity of 150mAh / g and a capacity retention rate of 96% after 200 cycles, with comprehensive performance reaching the industry-leading level.

[0063] The differences in performance caused by parameter adjustments in the preparation of lithium manganese iron phosphate cathode materials in this technical solution are as follows: In Example 2, the 20nm PDA layer enhances ion diffusion capability, increasing the high-temperature cycle retention rate at 45℃ to 97.5%, but with a slight capacity decrease (148mAh / g), indicating that a balance between high-temperature stability and energy density requirements needs to be achieved based on the application scenario. In Example 3, the 3:1 CNT / graphene ratio increases the compaction density to 2.4g / cm³, but excessive CNTs may hinder lithium-ion diffusion (capacity retention rate 95.8%), requiring further exploration of the synergistic mechanism between conductive network and ion transport. In Example 4, lowering the temperature to 700℃ in the high-temperature sintering step reduces energy consumption by 10%, but limited lattice integrity leads to a decrease in capacity (142mAh / g), making it suitable for cost-sensitive large-scale production scenarios. In Example 5, the 3nm Al2O3 layer increases the cycle retention rate to 98% (25℃), verifying the inhibitory effect of surface passivation on manganese dissolution, but the thickness of the Al2O3 layer needs to be controlled to avoid increased lithium-ion migration resistance.

[0064] Specifically, when a single carbon coating was used (in Comparative Example 1, when only glucose carbon source was used to prepare a single carbon coated lithium manganese iron phosphate cathode material, the capacity retention rate dropped sharply to 85%, proving that multi-level coating (PDA+CNT / graphene+Al2O3) is a necessary technical path to solve the contradiction between conductivity and manganese dissolution.

[0065] The lithium battery performance of Comparative Example 2 using traditional pure ferrous sulfate / manganese raw materials is similar to that of Example 1 (capacity retention rate of 95%), but the raw material cost increases by 35%, highlighting the economic and environmental advantages of titanium dioxide by-products (reducing waste disposal pressure by more than 30%).

[0066] Compared with existing technologies, the multi-stage coated lithium manganese iron phosphate cathode material and its preparation method provided by this invention have the following advantages: I. Raw Material Innovation: Resource utilization of titanium dioxide by-products achieves the dual goals of "cost reduction" and "green manufacturing"; II. Innovative Structural Design: A three-in-one technical solution consisting of multi-level coating (ion / electron synergistic transport) + gradient sintering (lattice / carbon layer synergistic stabilization) + ALD (surface passivation); III. Industrialization potential: Process parameters (such as ALD thickness and sintering temperature) can be flexibly adapted to the differentiated needs of power batteries (high energy density / long cycle life) and energy storage systems (low cost / high environmental friendliness).

[0067] In summary, unlike existing technologies, this invention provides a multi-level coated lithium manganese iron phosphate cathode material, its preparation method, and its application. The aforementioned lithium manganese iron phosphate cathode material has a core-shell structure, comprising a core, an inner coating layer surrounding the surface of the core, an intermediate coating layer surrounding the surface of the inner coating layer, and an outer coating layer surrounding the surface of the intermediate coating layer. The core comprises LiMn... 1-x Fe x The core-shell structure of the lithium manganese iron phosphate cathode material provided by this invention comprises a PO4 layer, an inner coating layer including a nitrogen-doped carbon layer, a middle coating layer including a three-dimensional carbon nanotube / graphene conductive network, and an outer coating layer including an Al2O3 layer. 1-x Fe x The PO4 layer and the nitrogen-doped carbon layer of the inner coating enhance the overall conductivity of the material; the three-dimensional carbon nanotube / graphene conductive network of the middle coating further constructs efficient electron transport channels, enhancing conductivity; and the Al2O3 layer of the outer coating specifically inhibits manganese dissolution, solving the problem of poor high-temperature cycling stability. Simultaneously, the above preparation method overcomes the limitations of traditional coating techniques in terms of precision and effectiveness, improving the material's electronic / ionic conductivity, inhibiting manganese dissolution, and enhancing high-temperature cycling stability, while also providing a superior technical path for industrial production through innovative processes.

[0068] It should be noted that all the above embodiments belong to the same inventive concept, and the descriptions of each embodiment have different focuses. Where the description in a particular embodiment is not detailed, please refer to the description in other embodiments.

[0069] The above embodiments merely illustrate implementation methods of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A multi-stage coated lithium manganese iron phosphate cathode material, characterized in that, The lithium manganese iron phosphate cathode material has a core-shell structure, which includes a core, an inner coating layer wrapped around the surface of the core, an intermediate coating layer wrapped around the surface of the inner coating layer, and an outer coating layer wrapped around the surface of the intermediate coating layer. The core includes LiMn 1-x Fe x The PO4 layer, the inner coating layer includes a nitrogen-doped carbon layer, the middle coating layer includes a three-dimensional carbon nanotube / graphene conductive network, and the outer coating layer includes an Al2O3 layer; 0 < x < 1.

2. A method for preparing a multi-stage coated lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, The method includes the following steps: S10, after mixing iron source, manganese source and phosphorus source, a precipitant is added to carry out a co-precipitation reaction to obtain iron-manganese-phosphorus precursor; S20, the iron-manganese-phosphorus precursor is mixed with a polydopamine solution and then subjected to a self-polymerization reaction to obtain a polydopamine-coated iron-manganese-phosphorus precursor. S30, the polydopamine-coated iron-manganese-phosphorus precursor, carbon nanotubes and graphene dispersion are ball-milled and composited to form a first conductive composite structure with a double layer coating the iron-manganese-phosphorus precursor. S40, the first conductive composite structure is mixed with a lithium source and then subjected to gradient sintering to obtain a second conductive composite structure with double-layer coating of lithium manganese iron phosphate. S50, after pulverizing the second conductive composite structure, an Al2O3 layer is deposited on the second conductive composite structure to obtain the lithium manganese iron phosphate cathode material.

3. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step S10: the iron source and the manganese source are selected from the iron-manganese solution obtained from the titanium dioxide production process, and the iron-manganese solution includes ferrous sulfate and manganese sulfate.

4. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step S10: the phosphorus source includes phosphoric acid or phosphate, the precipitant includes ammonia, and the reaction pH during the co-precipitation reaction is 2.5~3.

5.

5. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step S20: the temperature for the self-polymerization reaction is 40~80℃ and the time is 4~8h; the thickness of the polydopamine layer in the polydopamine-coated iron-manganese-phosphorus precursor is 10~30nm.

6. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 5, characterized in that, In step S30: the first conductive composite structure includes the iron-manganese-phosphorus precursor, the polydopamine layer coated on the surface of the iron-manganese-phosphorus precursor, and the three-dimensional carbon nanotube / graphene conductive network wrapped on the surface of the polydopamine layer.

7. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, The S40 step specifically includes: S401, the first conductive composite structure is mixed with a lithium source and then heated to 350~450℃ in an inert atmosphere and kept at that temperature for 1~3h to obtain a conductive network intermediate with the nitrogen-doped carbon layer. S402, the conductive network intermediate is heated to 600~800℃ in an inert atmosphere and kept at that temperature for 7~10h to obtain the second conductive composite structure.

8. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step S40: the second conductive composite structure includes the LiMn 1-x Fe x PO4 layer, coating the LiMn 1-x Fe x The nitrogen-doped carbon layer on the surface of the PO4 layer and the three-dimensional carbon nanotube / graphene conductive network wrapped around the surface of the nitrogen-doped carbon layer.

9. The method for preparing the multi-stage coated lithium manganese iron phosphate cathode material according to claim 2, characterized in that, In step S50: the D50 particle size of the second conductive composite structure after the pulverization treatment is 1~2μm; the thickness of the Al2O3 layer in the lithium manganese iron phosphate cathode material is 1~5nm.

10. The application of a lithium manganese iron phosphate cathode material prepared by the preparation method of the lithium manganese iron phosphate cathode material as described in claim 1 or the multi-level coated lithium manganese iron phosphate cathode material as described in any one of claims 2 to 9 in the preparation of lithium batteries.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate composite material and preparation method thereof, positive electrode material and lithium battery

    CN115207332A

  • Methods for making thick multilayer electrodes

    US20230155108A1